Visible-Light Communication with Lighting: RGB Wavelength Division Multiplexing OLEDs/OPDs Platform - Kim, Dowan; Park, Hyung Jun; Jung, Seo Hee; Pyo, Won Jun; Hassan, Syed Zahid; Sim, Hye Ryun; Lee, Jeong Hwan; Jee, Dong Woo; Chung, Dae Sung (Advanced Materials, 2024)
A multichannel/multicolor visible light communication (VLC) system using entirely organic components, including organic light emitting diodes (OLEDs) and organic photodiodes (OPDs), is developed to demonstrate indoor lighting applications where the integration of OLEDs and OPDs has significant potential. To achieve this, tricolor (Red/Green/Blue(R/G/B))-selective OPD arrays for the receiver and tricolor OLED arrays for the emitter are developed. For (R/G/B)-selective OPDs, a Fabry–Pérot electrode to enhance color selectivity and a thick junction structure to effectively accommodate a wide range of driving voltages are introduced. For tricolor OLEDs, fluorescent-emitting materials are used to enhance the operating frequency in addition to introducing a cavity structure to achieve narrow emission. Utilizing these spectrally refined tricolor OPDs/OLEDs, a VLC system is designed for indoor lighting applications, and a systematic analysis of their signal-to-interference ratio dependence on the distance or angle between the transmitter and receiver is performed. The study's findings indicate the importance of emission angle-dependent wavelength shift of the OLED and the luminosity function, which varies with wavelength, in the R/G/B mixed-white-light-based VLC systems. Finally, the feasibility of VLC using tricolor OPDs/OLEDs in the real-life context of indoor white-color lighting is demonstrated, showing that the transmitted data patterns well-matched the received data patterns.
Keywords: Communications systems; Data patterns; Indoor lightings; Lightemitting diode; Lighting applications; Organic light-emitting; Organic light-emitting diode; Organic photodiodes; Red green blues; White-lighting; organic light-emitting diode; organic photodiode; visible-light communication; white-lighting